Uso de plasma sanguíneo como terapia alternativa en las glándulas mamarias en vacas con mastitis subclínicas - Arteaga Ledesma, Rosalia Dayrobi (2024)
Subclinical mastitis affects the mammary glands and causes a loss in milk and economic production, which is why it is recommended to use alternative treatments because the vast majority of daily antibiotics have withdrawal time in milk production, which affects the owner. The present study was carried out with a population of 38 cows diagnosed with subclinical mastitis of the 52 cows with an incidence of 73.07%, the same ones that are under milking at the La Delia farm in the Pimocha parish. Which belong to a mestizo racial crossing. For the development of this research, a Completely Random Design (C.D.A.) was designated, which includes three treatments and five repetitions, following the specified additive linear model. The presence of subclinical mastitis was determined; as traces and slightly positive, and clinically as positive and very positive using the California test. An antibiogram was carried out on the control treatment group (T0) by which the molecules to which this group is susceptible to bacteriological agents were determined depending on the culture carried out in treatments 1 (T1) and 2 (T2), they were administered 3 ml and 5 ml of blood plasma respectively, and its effect was evaluated in comparison with the control treatment, resulting in that if a difference was observed in the bacteria from the initial culture to the final culture, the effect of blood plasma in the different treatments was also evaluated. . By determining the variables, it was evident that there were no significant differences between the presence of colonies of microorganisms with the dosage used in the treatments in the initial culture, given that the p value is greater than 0.05.